Book Review: Swarnavel Eswaran Pillai, Madras Studios: Narrative, Genre, and Ideology in Tamil Cinema. (June 2018) - Ingle, Hrishikesh
Swarnavel Eswaran Pillai, Madras Studios: Narrative, Genre, and Ideology in Tamil Cinema . New Delhi: SAGE, 2015, 332 pp., ₹852.00, ISBN 9789351501213.